Neurocysticercosis : a possible cause of epileptiform fits in people residing in villages served by the Bethanie clinic in the North West Province - Veary, C.M. (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2007.